Proceso de atención nutricional en paciente de sexo masculino de 70 años de edad con fibrosis pulmonar. - Morales Vera, Yolanda Marife (2022)
Pulmonary Fibrosis is characterized by respiratory distress or a gradual loss of lung function. The main treatment of this disease is the use of drugs, whose main function is to slow down the progression of the disease. This is accompanied by several symptoms such as lack of appetite and diarrhea resulting from weight loss, preventing optimal recovery of the patient. It translates to the fact that nutrition plays a fundamental role in the pathology, it is recommended to have a balanced diet, balanced in which all food groups are included; avoiding foods high in fat, salt and sugar, in the same way avoid alcoholic beverages. The present clinical case focused on the nutritional care process of a 70-year-old patient with pulmonary fibrosis, due to his pathology, he presents type I malnutrition and severe weight loss; It is caused by the signs and symptoms of the pathology in question. For its assessment, the necessary tests and nutritional assessment were carried out by anthropometric, biochemical, clinical, and dietary methods. Imaging studies (CT chest x-ray) showed a fibrotic pattern, in which 25% of the right lung is compromised. The nutritional intervention carried out helped us to improve the patient's weight and that the patient's quality of life is affected. A feeding plan was made according to the nutritional needs required by the patient. The follow-up and monitoring allowed us to show if there were improvements with the nutritional treatment prescribed to the patient, with respect to weight and symptoms presented, in the same way, albumin values.